Reducing airport emissions through aircraft gas turbine water injection at take-off - Block Novelo, David Alejandro; Igie, Uyioghosa (Cranfield University, 2018)
Airport-related air pollution has become a global concern. Around Mexico City’s Benito Juarez International Airport, the Nitrogen Oxide (NOx) levels double the concentration suggested by international authorities. At Heathrow Airport in London, airliners are charged more than £15.00 per kilogram of NOx emitted every time one of their aircraft takes-off. This contaminant is associated with respiratory diseases, and it has been recognized to damage the local vegetation and wildlife. Cooling the aircraft’s engine by compressor water injection is a way to reduce this pollutant by almost 50%. This study explains by means of an analytical method applied to the compressor, the physical mechanism behind the cooling of the thermodynamic cycle. The method is validated against other publications and used to evaluate the potential NOx decrease on a common aircraft’s power plant. It is shown how a 2-spool engine can benefit from a decrease in operating temperature in the order of 10%, which can lead to a NOx reduction of 45%. For an Airport like Heathrow, this can represent a reduction in total NOx emissions of 12%. The effects that water injection has on a gas turbine in terms of reduced temperature and increased ambient air humidity are isolated and quantified.
Keywords: Water Injection; Gas Turbine; NOx Emissions; Airport Pollution